Entre memórias impedidas e exercitadas : as violações dos direitos humanos na Ditadura Civil-Militar brasileira em disputa (1979-2022) - Amaro, Kátia Gomes da Silva (2023)
This thesis deals with the problem of disputes over the memory of the serious human rights violations that took place during the Brazilian Civil-Military Dictatorship (1964-1985), focusing on three dimensions that, in our opinion, have marked characteristics in this difficult trajectory: "impeded memory", "exercised memory" and "pedagogical memory". It is important to emphasize that there are a multiplicity of memories about the period, which have been re-signified over the years, in a dispute that has never ended. The main theoretical references used in this research come from authors such as Pollak (1989), Halbawachs (2004), Nora (1993), Ricoeur (2007) and Le Goff (2003) Huyssen (2014), Orlandi (2010). We used bibliographical research to understand the historical moment under study and the body of sources selected includes, above all, newspapers, reports from the National Truth Commission (CNV) and textbooks. In this sense, the methodology takes into account the specificities of each type of document. We have tried to show that transitional justice in Brazil has historically been impeded and has advanced much more as an exception than as a rule; that the Brazilian state has more than once tried to "forget", "conciliate" and "appease society", repeatedly preventing a thorough revision of the Amnesty Law;that the work of the CNV and the publication of its final report reflect the struggle of the Commission and the government in office at the time, up to the limits of what was possible at the time; and that, in the face of these limits, pedagogical memory appears as a utopian future for success in the battle for memory, which is still active. In this context, a didactic sequence was developed as a proposal for teaching history.